PENGARUH REMUNERASI, KOMPETENSI DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA DAN PRODUKTIVITAS PEGAWAI PT. PELINDO I CABANG DUMAI - Mukhlis, Muhammad; Suarman, Suarman; Garnasih, Raden Lestari (Jurnal Ekonomi, 2018)
This research aims to know how influence variable Remuneration, Competence and Career Development to Job Satisfaction dan Productivity in PT. Pelindo I Cabang Dumai. As for becoming population in this research is employee in        PT. Pelindo I Cabang Dumai. Amounting to 179 population and people in this research in made sampel amounting 124 by using slovin formula method. Technique of collecting data using questioner which contains statement based on the variable studied. Date analysis the used descriptive, despitefully also use quantitative analysis that was using doubled linear regresi and path analysis constructively SPSS of program version 21.00. From result of examination which have been conducted, test of regresi parsial (uji-t) structural 1 indicate that the Remuneration, Competence and Career Development have an effect on signifikan to Job Satisfaction. Beside test of regresi parsial (uji-t) structural 2 indicate that the Remuneration, Competence, Career Development and Job Satisfaction have an effect on signifikan to Produktivity. Result of test by using path analysis, known that variable Job Satisfaction can mediation influence Remuneration to Productivity, variable Job Satisfaction can mediation influence Competence to Productivity,and variable Job Satisfaction able to mediation influence of Career Developement to Productivity.